Desmodium molliculum (Kunth) DC (Fabaceae); Ethnobotanical, phytochemical and pharmacological profile of a Peruvian Andean plant. - Olascuaga-Castillo, Karyn; Rubio-Guevara, Susana; Valdiviezo-Campos, Juan Ernesto; Blanco-Olano, Cyntia (Ethnobotany Research and Applications, 2020)
Background: Desmodium molliculum commonly known as "dog's foot", "dog's leg", "food chanca", "muña" or "manayupa" is a Peruvian Andean plant that grows between 1000-3500 meters above sea level, it is a creeping herb belonging to the order Fabales, family Fabaceae and genus Desmodium. It is native to the Peruvian Andes, however, it is distributed from Mexico to South America. The purpose of this review is to provide comprehensive information on the botany, traditional uses, phytochemistry, pharmacological research, and toxicology of Desmodium molliculum. Methods: The information search for the preparation of this review was carried out in the search engines and databases Scielo, PubMed, Scopus and Google Academic, the inclusion criteria of the information were original and review articles, degree thesis and postgraduate studies, results were not ruled out by year of publication, the languages were reduced to Spanish and English. Results: Desmodium molliculum has exhibited a wide spectrum of pharmacological activities such as healing, antiasthmatic, anti-inflammatory, hepatoprotective, antibacterial, contraceptive, antioxidant activities, among others. Conclusions: It is concluded that from an ethnopharmacological point of view, it is necessary to investigate the biochemical and physiological mechanisms involved in the different biological effects exhibited by this species, especially the immunomodulatory, smooth muscle relaxant and contraceptive actions of Desmodium molliculum. It is also necessary to look for individual secondary metabolites responsible for these actions and to be able to study the mechanisms of action, bioavailability, pharmacokinetics and physiological pathways in sufficient detail. Key words: Desmodium, Fabaceae, ethnobotanical, traditional medicine, pharmacological activity.